Compostos bioativos de chás: comparação das infusões a quente e a frio - Rodrigues, Vanessa de Carvalho (2015)
Tea is one of the most consumed beverages in the world. Some biological functions of tea have been reported, such as anti-inflammatory, antioxidant, anti-allergic, and anti-obesity. These biological activities are associated, in part, to the antioxidant activity of chemical compounds present in tea, especially flavonoids and phenolic acids, however, the phenolic compounds are primarily responsible for the beneficial properties of tea. Thus, the total evaluation and quantification of individual phenolic compounds is essential to correlate its biological activity. The samples were evaluated green tea, chamomile, broom, Boldo, white, lemon, black and matte. In this study, flavonoids and phenolic compounds were quantified by spectrophotometry. The antioxidant capacity of phenolic extracts was evaluated by DPPH and ABTS•+ methods. Phenolic compounds were identified by high performance liquid chromatography (HPLC). Antimicrobial activity was determined by assessing the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The principal component analysis (PCA) and hierarchical cluster analysis (HCA) showed that it was not observed a clear distinction between the extraction methods. In this study, the cold extraction was more efficient in the extraction of bioactive compounds.